Social entrepreneurship as a collaborative practice: Literature review and research agenda - Sunna Kovanen (Journal of Entrepreneurship, Management and Innovation)
Purpose: The aim of this article is, firstly, to explore and structure the emerging research on collaboration in social entrepreneurship, and secondly to tackle the identified gaps in the literature with a research agenda based on the communities and networks of practice theory. Methodology: The article relies on a systematic literature review, which summarizes the existing evidence base and critically evaluates major theoretical approaches. The analytical focus is on ambiguity and scales of collaboration. Findings: Three main research strands have been identified: first, community and public sector collaboration focusing on the participatory initiation of services by local communities; second, collaboration for resources and employment focusing on power relations between established organizations; and third, network- and micro-level collaboration focusing on collaborative governance of complex networks. A vaguely contextualized and non-critical approach to social entrepreneurship remains prominent; however, recent studies on community and network collaboration present nuanced approaches to scalarity and ambiguity. Implications for theory and practice: Existing research could benefit from explicit and broader theorization of collaboration, the analysis of ambiguous experiences and contexts and attending to the interplay between daily practices and larger-scale institutional change. The paper presents a compiled reference base and gives directions about future research and practice re-thinking social enterprise as a collaborative endeavor. Originality and value: The article contributes to social entrepreneurship studies by structuring the field and enhancing critical theory on the topic.